As devolutivas escritas da coordenação pedagógica como promotoras de desenvolvimento profissional - Costa, Elenice Rosa da Silva (2023)
This research, with a qualitative approach, had the general objective of analyzing the feedback written by the pedagogical coordination to the teachers as a formative strategy that propels professional development. The theoretical foundation, which supports this study, is based on assumptions of authors who highlight the relationship between writing and the historical construction of the subject and as a construction of individual and collective memory, Freire (2003), Soligo and Prado (2017); registration as an intervention strategy in teacher training and reflection on pedagogical practice, Fujikawa (2012; 2017); the professional performance of the pedagogical coordinator as a trainer, articulator and transformer, Placco and Almeida (2010; 2016; 2017); the pedagogical coordinator as the main person responsible for the training and learning of adult teachers, Placco e Souza (2015; 2018) and writing as a professional attitude of educators/trainers, Lenner (2020). As procedures for production, we opted for document analysis, the application of a questionnaire and the organization of discussion groups. Pedagogical coordinators who work in early childhood education at a Regional Board of Education in the south of São Paulo participated in this study. The investigation of the data, inspired by the analysis of prose, as proposed by André (1983), express that the written feedbacks as a formative strategy, present a multifaceted character, considering the diversity of possibilities of interventions and referrals that coordinators and pedagogical coordinators make available to the teachers, and, as a driver of professional development, they present themselves as an action of double benefit, because when writing feedback promoting reflections and/or problematizing the teaching pedagogical practice, pedagogical coordinators also reflect aspects related to their work . Based on the results, it is understood that it is necessary to think about public policies that ensure conditions for continued in-service training and the professional performance of educational coordinators to occur in a qualified manner; that managers and professors value training moments as privileged situations for the construction of knowledge and that pedagogical coordinators constitute their professional identity, assuming teacher training as the center of their work.